2012
DOI: 10.1007/s11434-012-5245-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative crystal structure determination of griseofulvin: Powder X-ray diffraction versus single-crystal X-ray diffraction

Abstract: In an attempt to compare crystal structure determination from powder data and single-crystal data, crystal structure of griseofulvin (C 17 H 17 ClO 6 ) was tested by both powder and single-crystal X-ray diffraction. Lattice parameters of griseofulvin are α=90. 0°, a=b=8.9757 Å, c=19.9345 Å, V=1605.99 Å 3 from powder data coinciding with α=90.0°, a=b=8.9714 Å, c=19.8848 Å, V=1600.46 Å 3 from single-crystal data. Main processes of structure elucidating of griseofulvin by the two approaches were analyzed. Powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…Therefore, in this paper, we presented the crystal structure of compound 1 that were analyzed by both single-crystal X-ray diffraction (SXRD) and synchrotron radiation X-ray powder diffraction (PXRD), while the powder diffraction data were solved by the simulated annealing method and was further verified by rigid-body Rietveld refinement, and the single-crystal diffraction data were solved by direct methods and refined with full-matrix least-squares techniques [13][14][15][16]. Very little work had been done in comparing the crystal structure data, such as bond length and bond angle, obtained from these two approaches.Li and his co-workers reported a comparative study of the crystal structure data of griseofulvin obtained from SXRD and PXRD [17]. In this research, we showed an improved result with a sub-1% deviation between most of the crystal structure data of compound 1 obtained from PXRD and SXRD.…”
Section: Introductionmentioning
confidence: 53%
“…Therefore, in this paper, we presented the crystal structure of compound 1 that were analyzed by both single-crystal X-ray diffraction (SXRD) and synchrotron radiation X-ray powder diffraction (PXRD), while the powder diffraction data were solved by the simulated annealing method and was further verified by rigid-body Rietveld refinement, and the single-crystal diffraction data were solved by direct methods and refined with full-matrix least-squares techniques [13][14][15][16]. Very little work had been done in comparing the crystal structure data, such as bond length and bond angle, obtained from these two approaches.Li and his co-workers reported a comparative study of the crystal structure data of griseofulvin obtained from SXRD and PXRD [17]. In this research, we showed an improved result with a sub-1% deviation between most of the crystal structure data of compound 1 obtained from PXRD and SXRD.…”
Section: Introductionmentioning
confidence: 53%
“…The d-values were calculated using CuK α 1 radiation (λ = 1.540 56 Å). (Pan et al, 2012). MC/SA search algorithm in the Powder Solve package (Engel et al, 1999) was used to constantly adjust the conformation, position, and orientation of the trial model in a unit cell of gemcitabine.…”
Section: B Diffraction Data Collection and Reductionmentioning
confidence: 99%
“…There are three polymorphs (forms I, II, and III) that have been reported for griseofulvin (33). Amorphous griseofulvin prepared by quench cooling with a melting period less than 10 min has been consistently demonstrated to recrystallize to the crystalline form I, which consists of a tetragonal cell and a P4 1 space group that is noncentrosymmetric (29,30,34).…”
Section: Introductionmentioning
confidence: 98%